2017
DOI: 10.4103/0253-7176.198937
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Online Neuromodulation Using Transcranial Alternating Current Stimulation in Schizophrenia

Abstract: Abnormalities in resting and event-related brain oscillations are known to be associated with cognitive deficits in schizophrenia. Transcranial alternating current stimulation (tACS) modulates these rhythms across the neuronal circuits and could have a potential therapeutic role in psychiatric disorders. In this report, we describe, for the first time, application of online tACS in a schizophrenia patient with working memory deficits. This case report supports the feasibility and potential utility of online tA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 13 publications
0
38
0
1
Order By: Relevance
“…Finally, multicentre double-blind clinic trials could be fostered to investigate larger sample sizes. This may also facilitate the utility of different stimulation protocols in different patients or within the same individuals to rule out a stimulation effect per se [4,125,131,150] and to question the potential synergism of different stimulation parameters, respectively (for more technical guidance: [12,[205][206][207]).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, multicentre double-blind clinic trials could be fostered to investigate larger sample sizes. This may also facilitate the utility of different stimulation protocols in different patients or within the same individuals to rule out a stimulation effect per se [4,125,131,150] and to question the potential synergism of different stimulation parameters, respectively (for more technical guidance: [12,[205][206][207]).…”
Section: Discussionmentioning
confidence: 99%
“…First, in schizophrenia, frontal alpha tACS was promising as an add-on treatment for persistent delusions [ 128 ] and was capable of normalizing disturbed alpha oscillations correlated with a decrease in auditory hallucinations [ 4 , 131 ]. On the other hand, frontal gamma tACS has not shown effects so far [ 125 , 129 ]. Case reports revealed that frontal theta tACS could be helpful for improving clinical symptoms, even in schizophrenia with clozapine resistance [ 125 127 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations